Evaluating Psychometric Properties of the International Knee Documentation Committee Subjective Knee Form in a Heterogeneous Sample of Post-Operative Patients - Ryan D Richardson; Madeline P Casanova; Ashley J Reeves; Seungho Ryu; Adam C Cady; Russell T Baker (International Journal of Sports Physical Therapy, 2023)
# Background